Enhanced photoelectrocatalytic hydrogen production activity of SrTiO3–TiO2 hetero-nanoparticle modified TiO2 nanotube arrays. (17th August 2015) - Wu, Zhi; Su, Yufeng; Yu, Jiangdong; Xiao, Wang; Sun, Lan; Lin, Changjian
Abstract SrTiO3–TiO2 hetero-nanoparticle modified TiO2 nanotube arrays (ST–TiO2 NTAs) were constructed by following these steps: firstly, highly ordered TiO2 nanotube arrays (TiO2 NTAs) were synthesized directly on Ti foils through electrochemical oxidation, then SrTiO3–TiO2 nanoparticles were deposited on the TiO2 NTAs using two-step hydrothermal treatment. SrTiO3–TiO2 nanotube arrays (S–TiO2 NTAs) were also prepared by directly hydrothermal treatment of TiO2 NTAs for comparison. The photoelectrocatalytic hydrogen production activities of all the samples were evaluated by using ethylene glycol as a sacrificial reagent in water under a 300 W xenon arc lamp. The photoelectrocatalytic hydrogen production rate of TiO2 NTAs can be significantly improved by modifying SrTiO3–TiO2 hetero-nanoparticles and achieved a greatly promoted value of 314.9 μmol cm−2 h−1 which was 2.1 times higher than that of the unmodified TiO2 NTAs. Compared to S–TiO2 NTAs, ST–TiO2 NTAs showed a 32.8% increase in hydrogen production rate. Furthermore, SrTiO3–TiO2 hetero-nanoparticle modified TiO2 nanotube arrays exhibited excellent stability and was facile to be safely reused. The improvement of photocatalytic hydrogen production efficiency is attributed to the difference of the conduction band potential between TiO2 and SrTiO3 in SrTiO3–TiO2 hetero-nanoparticles, thereby boosting the transfer and separation of the photogenerated electron–hole pairs.